Atuação e Formação de Músicos de Casamento na Cidade de Uberlândia-MG - Simão, Diego Caaobi dos Santos (2019)
This Master's research is about a case study with five musicians from Uberlândia (MG), whose general objective was to understand how it goes the performance of musicians who play at weddings in Uberlândia-MG, at the entrance, permanence and projection, in their acting space. We also sought to identify strategies used by these musicians to build their professional performance in this professional niche and to understand how they manage their own musical formation for performance and to belong to this universe as wedding musicians, how they adapt, reformulate knowledge in their music-social practices, create personal solutions, and what are their dilemmas and their processes of adaptation to the issues of "being a musician" in the context of their professional performance. The concept of professional socialization elaborated by Dubar (2005; 2012) was the basis for analyzing the performance of these musicians, as well as the conception of music as a social practice (BOURDIEU, 2004). It is concluded that the musicians inserted in the groups that play in marriage are immersed in a plural professional performance, which demands diverse music social skills, considering the moments in which the grooms hire musicians to compose the scenarios of the wedding event. In this sense, wedding musicians undergo an adaptation that is both personal and musical, and also where, on the one hand, various types of conflicts and dilemmas are housed. Being between what they want to do as musicians and what the demands of marriage require, questions about the recognition of their performance, the commitment to an activity that is intended to make a dream come true, issues of being a musician and being a professional musician are also part of this context.